Catastrophic health expenditure among cancer patients attending Bhaktapur Cancer Hospital, Nepal. - Bhattarai, Laxmi (2020)
ABSTRACT: Cancer is expected to rank as the leading cause of death and the single most important barrier to increasing life expectancy in every country of the world. Catastrophic Health Expenditure is kept as one of the monitoring indicators of Universal Health Coverage. Ministry of Health has given financial help through its medical aid policy to people lying below poverty line but there are many people who lie just above poverty line and they are the one who suffer the most. The objective of this study was to assess catastrophic health expenditure among cancer patients attending Bhaktapur Cancer Hospital, Nepal. A hospital based quantitative descriptive cross-sectional study design was carried out using systematic random sampling method to select 201 cancer patients who were receiving treatment from Bhaktapur Cancer Hospital. Chi-square test and binary logistic regression were done in SPSS version 20 to find out the associated factors of catastrophic health expenditure at p<0.05. Prevalence of CHE was reduced to 87.6 percent from 95 percent when threshold level was increased from 10 percent to 25 percent. The mean cost of out of pocket expenditure of medical care was NRs 38,170. Participants with catastrophic health expenditure and non-catastrophic health expenditure showed majority of the percentage share of out of pocket expenditure in chemotherapy (36.79% and 44.16%) followed by lab and diagnostic charges (19.97% and 23.6%). Participants with duration of treatment more than six months was 3.086 times more likely to perform CHE (AOR=3.086, 95% CI=1.227- 7.75) than duration of treatment less than six months and participants receiving chemotherapy as a highest level of care were 2.478 times more likely to perform CHE (AOR= 2.478, 95% CI= 0.485- 4.51) than participants receiving any other treatment like palliative, radiation or supportive. There was high catastrophic health expenditure and majority of the percentage share of cost was in chemotherapy. Government needs to provide individuals with more financial protection against the consequences of cancer like compulsory enrollment of all citizens in health insurance. Health related policy makers need to develop support policies for cancer patients and at the same time aim at reducing their treatment expenses.